Proceedings of the 37th IEEE/ACM International Conference on Automated Software Engineering 2022
DOI: 10.1145/3551349.3556957
|View full text |Cite
|
Sign up to set email alerts
|

VITAS : Guided Model-based VUI Testing of VPA Apps

Abstract: The flourishing ecosystem centered around voice personal assistants (VPA), such as Amazon Alexa, has led to the booming of VPA apps. The largest app market Amazon skills store, for example, hosts over 200,000 apps. Despite their popularity, the open nature of app release and the easy accessibility of apps also raise significant concerns regarding security, privacy and quality. Consequently, various testing approaches have been proposed to systematically examine VPA app behaviors. To tackle the inherent lack of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…VerHealth [53] analyzed 813 health-related skills on the Amazon Alexa platform. Vitas [42] interacted with 41,581 skills and found that 51% of skills suffered from problems such as unexpected exit/start and privacy violation. SkillDetective [59] identified 6,079 policy-violating skills in the current skills stores by evaluating skills' conformity to more than 50 different policy requirements.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…VerHealth [53] analyzed 813 health-related skills on the Amazon Alexa platform. Vitas [42] interacted with 41,581 skills and found that 51% of skills suffered from problems such as unexpected exit/start and privacy violation. SkillDetective [59] identified 6,079 policy-violating skills in the current skills stores by evaluating skills' conformity to more than 50 different policy requirements.…”
Section: Related Workmentioning
confidence: 99%
“…Distinction from existing works. SkillScanner distincts itself from existing policy violation detection works (including SkillExplorer [39], VerHealth [53], Vitas [42] and SkillDetective [59]) in three ways. First, different from recent skill testing tools that utilize dynamic analysis and can only detect violations exercised by run-time inputs, SkillScanner is the first-of-its-kind static analysis tool and it detects more possible violations/inconsistencies in the code.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The privacy concerns of the VPA app ecosystem have also raised high attention from the research community. A line of research has been dedicated to detecting the runtime information gathering behaviors of VPA apps [35,47,79]. Some recent studies [81,82] propose to examine the compliance between VPA apps' data handling behaviors and the statements in their privacy policies.…”
Section: Introductionmentioning
confidence: 99%